Steven Osika: capstone - Osika, Steven, artist (Colorado State University. Libraries, 2017)
The artist's statement: The idea at hand focuses on patterns within natural environments and the recurring forms that take place through perfect geometries. The creative process is centered around the pinecone and how the pinecone itself is a representation of this perfect geometry. The system of sequences is naturally designed to find the most efficient way to form a physical object so that its functionality is served to its maximum potential throughout its lifetime. Certain shapes may form and a specific number of those shapes will grow to show a pattern that exemplifies what we call the "Fibonacci Sequence." This sequence is present in a majority of natural forms that we see around us, which further touches on the idea of pattern. The forms are not random by any means. These fundamental ideas allow an individual to better understand the natural world as well as have a better appreciation for it.
Fibbonacci in nature
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: photo image making